John Martin Vanharlingen address - Vanharlingen, John Martin
Address entitled, "The Revival of Learning," delivered by Vanharlingen to the Franklin Association of Philadelphia.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Franklin Association of Philadelphia; Education; Learned institutions and societies -- Pennsylvania -- Philadelphia